2019
DOI: 10.1016/j.immuni.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Recruitment to the Intestinal Stem Cell Compartment Drives Immune-Mediated Intestinal Damage after Allogeneic Transplantation

Abstract: Highlights d The crypt base region is the primary intestinal location invaded by T cells after BMT d T cell infiltration does not correlate with overall intestinal vascular architecture d Allo donor T cells rapidly access the ISC compartment and directly interact with ISCs d MAdCAM-1 localizes to crypt region vessels and directs T cells to the ISC compartment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 71 publications
3
71
0
Order By: Relevance
“…CD4 + T cells have been previously reported to localize to intestinal crypts and induce aGVHD by destroying cells within this niche ( 23 25 ). Consistent with this finding, we observed decreased colon length and increased goblet cell and crypt loss in aGVHD mice as compared with syngeneic controls ( Figure 9, A–D ; P < 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + T cells have been previously reported to localize to intestinal crypts and induce aGVHD by destroying cells within this niche ( 23 25 ). Consistent with this finding, we observed decreased colon length and increased goblet cell and crypt loss in aGVHD mice as compared with syngeneic controls ( Figure 9, A–D ; P < 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated that both CD4 + and CD8 + T cells had the potential to mediate injury to the ISC compartment in graft-versus-host disease model. The disease-causing T cells, after bone marrow transplantation (BMT)-mediated GI damage, targets the ISC niche as the primary site in the intestine under three-dimensional imaging examination ( 67 ). In addition, the recruitment of disease-causing T cells to the crypt base region resulted in the loss of ISC that expresses both the major histocompatibility complex class (MHC) I and II ( 67 ).…”
Section: Intestinal Stem Cell Nichementioning
confidence: 99%
“…The disease-causing T cells, after bone marrow transplantation (BMT)-mediated GI damage, targets the ISC niche as the primary site in the intestine under three-dimensional imaging examination ( 67 ). In addition, the recruitment of disease-causing T cells to the crypt base region resulted in the loss of ISC that expresses both the major histocompatibility complex class (MHC) I and II ( 67 ). In a similar report, another study explored the changes in the ISC niche using T cell-mediated injury in graft-versus-host disease (GVHD) model in vivo and intestinal organoid-T cell co-culture in vitro ( 55 ).…”
Section: Intestinal Stem Cell Nichementioning
confidence: 99%
“…Regarding the above phenomenon, the new niche for the implanted iLCs may play a vital role . In the early stage of transplantation, the cells may need to adapt to the new environment, and therefore, they maintain a slightly low activity. The activity of these implanted iLCs began to increase gradually approximately one week later.…”
Section: Discussionmentioning
confidence: 99%